(untitled) (Itinera, 2013)
The chiastic nexus between Socrates’ irony and its ridiculousness in the eyes of Thrasymachus permits to reformulate the importance of laughter as an ambiguity-laden philosophical subject. Taking into account the functions attributed to laughter by many authors – particularly Plato, Bergson, Kant, and Plessner – this paper investigates the relationship among laughter, approval, and displeasure, suggesting that the ambiguity of laughter comes out from a temporary breakdown either in the consolidated frames of meaning, or in the attempts to suggest new ones.